Exosomal circ_0006896 promotes AML progression via interaction with HDAC1 and restriction of antitumor immunity - Can Can; Xinyu Yang; Hexiao Jia; Hanyang Wu; Xiaodong Guo; Yihong Wei; Ziting Jia; Wancheng Liu; Amin Zhang; Na He; Hailei Zhang; Daoxin Ma (Molecular Cancer)
Abstract Background Drug resistance and immune escape continue to contribute to poor prognosis in AML. Increasing evidence suggests that exosomes play a crucial role in AML immune microenvironment. Methods Sanger sequencing, RNase R and fluorescence in situ hybridization were performed to confirm the existence of circ_0006896. The role of circ_0006896 in the progression of AML was assessed by in vitro and in vivo functional experiments. Flow cytometry, RT-qPCR and adoptive T cell-transfer immunotherapy were conducted to assess the function of exosomal circ_0006896 in CD8+ T cell dysfunction. RNA pull-down assay, mass spectrometry, immunofluorescence, co-immunoprecipitation and western blot were performed to identify and confirm the circ_0006896 interacting proteins. Results CircRNA expression patterns in exosomes differ significantly between AML and controls compared to lncRNAs or mRNAs. A new crucial exosomal circRNA, circ_0006896, is upregulated in both AML cells and exosomes and correlates with the prognosis and relapse of AML. In vitro and in vivo studies suggest that circ_0006896 significantly promotes AML cell proliferation, reduces chemotherapy sensitivity, and more importantly, impairs the efficacy of adoptive T cell-transfer immunotherapy. Mechanistically, circ_0006896 physically interacts with the catalytic domain of histone deacetylase HDAC1, decreasing histone H3 acetylation, and impairing the transcription of genes involved in arachidonic acid metabolism, ultimately inhibiting lipid peroxidation and ferroptosis in AML cells. Exosomal circ_0006896 disrupts CD8+ T cell function by interacting with HDAC1, impairing LEF1 transcription and subsequently decreasing the expression of cytotoxic molecules IFN-γ and Granzyme B. Conclusions We demonstrate a self-driven progression mediated by exosomal circRNAs and CD8+ T cells, highlighting the potential of targeting circRNAs in AML immunotherapy.